Midwives Knowledge, Infrastructure Facilities, and Supervision-Monitoring of Immunization Management in West Bandung Regency - Fathia Rizki; Adjat Sedjati Rasyad; Herry Garna (Universitas Islam Bandung, 2020)
The midwife mostly carries out immunization activities in the health care unit. The midwife is an injection officer and responsible for planning, transportation, storage, and vaccine usage. This study aims to determine the effect of knowledge midwives on vaccine management, infrastructure availability, and immunization management supervision by midwives in the West Bandung regency. A total of 38 self-employed midwives who met the inclusion criteria were taken from the West Bandung regency from July 2017 to February 2018. This research was an observational analytical research with a cross-sectional design. Analysis of bivariate data using correlation regression. The multivariate correlation using multiple linear regression. The result showed that midwife knowledge about vaccine management influenced 33.3% (p=0.0001), infrastructure 54.2% (p=0.010), and the supervision 34.65% (p=0.010) to managing immunization. The linear regression test between the variables shows that the determinant factor in managing is the facilities' immunization availability (beta coefficient=0.615). In conclusion, midwife knowledge, infrastructure facilities, and supervision on immunization management in West Bandung regency affected the immunization processes. PENGETAHUAN BIDAN, SARANA PRASARANA, DAN SUPERVISI-PEMANTAUAN MANAJEMEN IMUNISASI DI KABUPATEN BANDUNG BARATKegiatan imunisasi sebagian besar dilakukan oleh bidan di unit pelayanan kesehatan. Bidan sebagai petugas injeksi bertanggung jawab atas perencanaan, pengangkutan, penyimpanan, dan penggunaan vaksin. Penelitian ini bertujuan mengetahui pengaruh pengetahuan bidan terhadap manajemen vaksin, ketersediaan sarana prasarana, dan supervisi manajemen imunisasi oleh bidan di Kabupaten Bandung Barat. Sebanyak 38 bidan wiraswasta yang memenuhi kriteria inklusi diambil dari Kabupaten Bandung Barat periode Juli 2017 hingga Februari 2018. Penelitian ini merupakan penelitian analitik observasional dengan desain cross-sectional. Analisis data bivariat menggunakan correlation regression. Korelasi multivariat menggunakan multiple linear regression. Hasil penelitian menunjukkan bahwa pengetahuan bidan tentang pengelolaan vaksin berpengaruh sebesar 33,3% (p=0,0001), sarana prasarana 54,2% (p=0,010), dan supervisi 34,65% (p=0,010) terhadap pengelolaan imunisasi. Uji linear regression antarvariabel menunjukkan bahwa faktor determinan dalam pengelolaan adalah ketersediaan sarana prasarana imunisasi (koefisien beta=0,615). Simpulan, pengetahuan bidan, sarana prasarana, dan supervisi tentang manajemen imunisasi di Kabupaten Bandung Barat berpengaruh terhadap proses imunisasi.